2013
DOI: 10.1007/s10661-013-3202-7
|View full text |Cite
|
Sign up to set email alerts
|

Influence of elevated carbon dioxide and temperature on belowground carbon allocation and enzyme activities in tropical flooded soil planted with rice

Abstract: Changes in the soil labile carbon fractions and soil biochemical properties to elevated carbon dioxide (CO2) and temperature reflect the changes in the functional capacity of soil ecosystems. The belowground root system and root-derived carbon products are the key factors for the rhizospheric carbon dynamics under elevated CO2 condition. However, the relationship between interactive effects of elevated CO2 and temperature on belowground soil carbon accrual is not very clear. To address this issue, a field expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 55 publications
2
31
0
Order By: Relevance
“…Root biomass and tiller number of wild rice were reported to significantly increase under elevated CO 2 (Inubushi et al, 2003;Kim et al, 2003). Accordingly, increased carbon input in the rhizosphere soil though rice root exudates and rhizodeposition was observed under elevated CO 2 (Bhattacharyya et al, 2013;Okubo et al, 2014). As microbial communities in soil can be generally mediated by carbon substrate availability, an increase in below-ground carbon input could bring changes in soil microbial biomass under climate change conditions (Rakshit et al, 2012).…”
Section: Responses Of Aoa and Aob Communities To Elevated Co 2 And Wamentioning
confidence: 99%
See 1 more Smart Citation
“…Root biomass and tiller number of wild rice were reported to significantly increase under elevated CO 2 (Inubushi et al, 2003;Kim et al, 2003). Accordingly, increased carbon input in the rhizosphere soil though rice root exudates and rhizodeposition was observed under elevated CO 2 (Bhattacharyya et al, 2013;Okubo et al, 2014). As microbial communities in soil can be generally mediated by carbon substrate availability, an increase in below-ground carbon input could bring changes in soil microbial biomass under climate change conditions (Rakshit et al, 2012).…”
Section: Responses Of Aoa and Aob Communities To Elevated Co 2 And Wamentioning
confidence: 99%
“…Effects had been frequently reported of CO 2 enrichment on rice ecosystem function including rice grain yield and quality, plant nutrients uptake and greenhouse gas emission (Hasegawa et al, 2013;Usui et al, 2014;Tokida et al, 2011). Correspondingly, activity and community composition of ammonia oxidizer in rice rhizosphere could be affected by elevated CO 2 through root exudates and rhizodeposition as well as soil organic carbon (Bhattacharyya et al, 2013;Okubo et al, 2014). The changes to nitrifying activity of agricultural soils under elevated atmospheric CO 2 and warming conditions had been shown to depend on soil pH, inorganic N availability, and ammonia oxidizer community structure and abundance, but these changes were difficult to correlate with those in nitrifying activity (Yao et al, 2011;Long et al, 2012).…”
Section: Introductionmentioning
confidence: 98%
“…The increase in [CO 2 ] is expected to enhance the growth and yield of C3 crops, including rice (29). Previous studies reported that increases in [CO 2 ] quantitatively and qualitatively altered the release of labile sugars, organic acids, and amino acids from plant roots (2, 6), which may influence the activity of rhizospheric and root–associated microbes, including methanogenesis (18). Tokida et al (32, 33) reported that the emission of CH 4 from paddy fields was significantly increased by [CO 2 ] and/or temperature elevations.…”
mentioning
confidence: 99%
“…High temperatures can inhibit photosynthesis, decrease photosynthesized C fixation and increase photosynthetically-fixed C flow from aboveground to belowground parts (Rennenberg et al 2006;Bhattacharyya et al 2013). However, sufficient soil moisture can offset the negative effect caused by high temperatures (Bassirirad et al 1991;Kuzyakov and Gavrichkova 2010), such as flooded pot conditions during reed growth.…”
Section: Percentagementioning
confidence: 99%